Electrodeposition of Iridium Oxide Nanoparticles for pH Sensing Electrodes. Issue 9 (1st January 2016) - Khalil, Munawar; Wang, Sai; Yu, Jianjia; Lee, Robert L.; Liu, Ning
Abstract : This paper reports the results of an experiment on the synthesis and electrodeposition of iridium oxide nanoparticles for the fabrication of a pH sensor. Iridium oxide nanoparticles with mean diameter in the range of 1–2 nm were successfully synthesized and electrodeposited on stainless steel substrate by cyclic voltammetry. It was observed that the surface of the deposited iridium oxide film exhibited porous and rough surface morphology. The iridium oxide electrode thus prepared displayed excellent pH sensitivity, obtaining super-Nernstian behavior with pH sensitivity value of −72.6 mV/pH.